2018
DOI: 10.1246/bcsj.20170313
|View full text |Cite
|
Sign up to set email alerts
|

Average Intermolecular Distances and Dynamics of Ruthenium-Containing Organometallic Ionic Liquids Studied by Nuclear Overhauser Effects between 19F and 1H Nuclei and NMR Relaxation Rate Measurements

Abstract: The physical properties of organometallic ionic liquids containing cationic ruthenium sandwich complexes {[Ru(C5H5)(C6H5R)]X; R = OCH(C4H9)2, OCH(C2H5)(C6H13); X = N(SO2CF3)2, N(SO2F)2} are dependent on the substituents. To obtain detailed information about the motional states and configurations of the constituent ions of these ionic liquids, we performed one-dimensional (1D) heteronuclear Overhauser enhancement spectroscopy (HOESY) NMR experiments and the standard relaxation rate (1/T1 and 1/T2) measurements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In these ILs, branched substituents increase the viscosity, compared with linear substituents. NMR spectroscopic studies have shown that this tendency correlates with the motion of the alkyl substituents [15d] . Similarly, in the PF 6 and CF 3 BF 3 salts of 5 c , the racemate has a lower melting point than the chiral salt, where these salts formed a conglomerate and racemic compound, respectively [19] .…”
Section: Design and Synthesis Of Organometallic Ionic Liquidsmentioning
confidence: 96%
“…In these ILs, branched substituents increase the viscosity, compared with linear substituents. NMR spectroscopic studies have shown that this tendency correlates with the motion of the alkyl substituents [15d] . Similarly, in the PF 6 and CF 3 BF 3 salts of 5 c , the racemate has a lower melting point than the chiral salt, where these salts formed a conglomerate and racemic compound, respectively [19] .…”
Section: Design and Synthesis Of Organometallic Ionic Liquidsmentioning
confidence: 96%